2010
DOI: 10.1111/j.1469-8137.2010.03207.x
|View full text |Cite
|
Sign up to set email alerts
|

An endoplasmic reticulum response pathway mediates programmed cell death of root tip induced by water stress in Arabidopsis

Abstract: Summary• Drought induces root death in plants; however, the nature and characteristics of root cell death and its underlying mechanisms are poorly understood. Here, we provide a systematic analysis of cell death in the primary root tips in Arabidopsis during water stress.• Root tip cell death occurs when high water deficit is reached. The dying cells were first detected in the apical meristem of the primary roots and underwent active programmed cell death (PCD). Transmission electron microscopic analysis shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 57 publications
10
113
0
1
Order By: Relevance
“…8,10,13 Disruption of ROS metabolism alters a variety of physiological processes, including cell death, leaf senescence and organ development. 8,11 Measurements of cell death by electrolyte leakage assays and trypan blue staining showed that after drought stress treatments, electrolyte leakage was slightly higher in the 35S:4ΔC plants but lower in the ntl4-1 mutants than that in Col-0 plants.…”
Section: Regulation Of Reactive Oxygen Species Generation Under Drougmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,13 Disruption of ROS metabolism alters a variety of physiological processes, including cell death, leaf senescence and organ development. 8,11 Measurements of cell death by electrolyte leakage assays and trypan blue staining showed that after drought stress treatments, electrolyte leakage was slightly higher in the 35S:4ΔC plants but lower in the ntl4-1 mutants than that in Col-0 plants.…”
Section: Regulation Of Reactive Oxygen Species Generation Under Drougmentioning
confidence: 99%
“…8,9 Drought stress stimulates ROS production, inducing programmed cell death in the root tips and enhancing drought tolerance through modification of the root system. 10 Increased ROS levels also induce leaf senescence, contributing to the maintenance of water balance within the whole plant and nutrient remobilization to the youngest leaves or sink organs. 11 We found that the NTL4 gene is induced in the presence of H 2 O 2 , suggesting that the NTL4 gene would be related with ROS response and/or signaling.…”
mentioning
confidence: 99%
“…We have previously shown that plants are able to stimulate lateral root development with enhanced stress tolerance through programmed cell death of the root apical meristem (RAM) of the primary roots under severe water stress. 2 Recently, we reported that under mild and moderate water stresses, plant primary roots undergo root tip swelling and RAM premature differentiation resulting in cessation of the primary root growth. 3 We demonstrated that the RAM premature differentiation of primary roots and subsequent lateral formation are directly correlated to plant stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the water deficit triggers PCD not only in green tissues but also in plant root tips. Apical meristem cells of primary roots undergoing PCD, demonstrate increased size of vacuole, degradation of organelles and the collapse of plasma membrane [188].…”
Section: Drought Stress -Soil Water Deficitmentioning
confidence: 99%